2011
DOI: 10.4103/0253-7613.83114
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Momordica charantia on oxidative stress-induced perturbations in brain monoamines and plasma corticosterone in albino rats

Abstract: Objectives:The objective of this study was to evaluate the antistress activity of Momordica charantia (MC) fruit extract on stress-induced changes in albino rats and also to explore attenuating effects of MC on in vitro lipid peroxidation in rat brain.Materials and Methods:In this study, Wistar albino rats (180–200 g) were used. Plasma corticosterone and monoamines—5-hydroxy tryptamine (5-HT), norepinephrine (NE), epinephrine (E) and dopamine (DA) in cortex, hypothalamus and hippocampus regions of brain were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Pretreatment with MC significantly reverts acute stress (immobilization for 150 min once only)-induced changes in levels of brain monoamine (5-hydroxytryptamine, norepinephrine, epinephrine, and dopamine) and the level of plasma corticosterone. This study has shown that the anti-stress activity of MC might be due to its anti-oxidant potential [104] . Nerurkar et al have investigated the neuroprotective effects of MC on a high-fat diet (HFD)-associated blood-brain barrier (BBB) disruption, stress and neuroinflammatory cytokines in C57BL/6 female mice.…”
Section: Introductionmentioning
confidence: 99%
“…Pretreatment with MC significantly reverts acute stress (immobilization for 150 min once only)-induced changes in levels of brain monoamine (5-hydroxytryptamine, norepinephrine, epinephrine, and dopamine) and the level of plasma corticosterone. This study has shown that the anti-stress activity of MC might be due to its anti-oxidant potential [104] . Nerurkar et al have investigated the neuroprotective effects of MC on a high-fat diet (HFD)-associated blood-brain barrier (BBB) disruption, stress and neuroinflammatory cytokines in C57BL/6 female mice.…”
Section: Introductionmentioning
confidence: 99%
“…Neurotransmitters including noradrenaline (NA), dopamine (DA), and 5-hydroxytryptamine (5-HT) are the important biogenic monoamines. Under stress condition, NA and 5-HT will be highly elevated [ 2 , 3 ]. However, extreme stress can cause impaired dopamine neurons [ 1 ] and collapse the homeostasis which may lead to various psychotic disorders including immunosuppression, hypertension, anxiety, endocrine disorder, and behaviour disorder [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Herbal medicines have been proposed as a cheaper and safer potential antistress agent. For examples, Withania somnifera, Piper longum, Momordica charantia, and Asparagus racemosus have been reported to have adaptogenic effect [ 2 , 3 , 5 ]. Legumes have also received great attention due to the presence of phytochemicals and their bioactivities.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, this is the first report which states that Type I ribosomal inactivating proteins derived from dietary bitter melon possess HDACi activity and can selectively induce apoptosis in premalignant and malignant prostate cells and inhibit human prostate cancer cell growth in vivo. [136,137] Inflammation and bitter melon Inflammation is a complicated immune process that can be defined by the sequential release of mediators such as pro-inflammatory cytokines, including interleukin (IL)-1, tumour necrosis factor (TNF), interferon (IFN)-c, IL-6, IL-12, IL-18, and the granulocyte-macrophage colony stimulating factor. Inflammation is settled by anti-inflammatory cytokines such as IL-4, IL-10, IL-13, IFN-a, and the transforming growth factor (TGF)-b.…”
Section: Antioxidant and Antiinflammatory Activitymentioning
confidence: 99%